Elevated baseline expression of seven virulence factor RNA transcripts in visceralizing species of Leishmania: a preliminary quantitative PCR study. (May 2022) - Mukkala, Avinash Naraiah; Kariyawasam, Ruwandi; Lau, Rachel; Valencia, Braulio M.; Llanos-Cuentas, Alejandro; Boggild, Andrea K.
Introduction: Leishmaniasis is a neglected tropical disease that manifests as three major disease phenotypes: cutaneous, mucocutaneous, and visceral. In this preliminary study, we quantified virulence factor (VF) RNA transcript expression in Leishmania species, stratified by geographic origin and propensity for specific disease phenotypes. Methods: Cultured promastigotes of 19 Leishmania clinical and ATCC isolates were extracted for total cellular RNA, cDNA was reverse transcribed, and qPCR assays were performed to quantify VF RNA transcript expression for hsp23, hsp70, hsp83, hsp100, mpi, cpb, and gp63 . Results: Comparison of visceralizing species (Leishmania donovani, Leishmania chagasi, and Leishmania infantum) versus non-visceralizing species [Leishmania (Viannia) spp., Leishmania tropica, Leishmania major, Leishmania mexicana, and Leishmania amazonensis] revealed a significantly greater pooled transcript expression for visceralizing species (p = 0.0032). Similarly, Old World species demonstrated significantly higher VF RNA transcript expression than New World species (p = 0.0015). On a per-gene basis, species with a propensity to visceralize ubiquitously expressed higher levels of gp63 (p = 0.005), cpb (p = 0.0032), mpi (p = 0.0032), hsp23 (p = 0.0039), hsp70 (p = 0.0032), hsp83 (p = 0.0032), and hsp100 (p = 0.0032). Conclusion: Here, we provide quantitative, preliminary evidence of elevated VF RNA transcript expression driven largely by the visceralizing causative species of Leishmania . This work highlights the extensive heterogeneity in pathogenicity mechanisms between Leishmania species, which may partly underpin the fatal progression of visceral leishmaniasis.